2022
DOI: 10.1177/10742484211055639
|View full text |Cite
|
Sign up to set email alerts
|

IV Sodium Ferric Gluconate Complex in Patients Hospitalized Due to Acute Decompensated Heart Failure and Iron Deficiency

Abstract: Background: Patients suffering from heart failure (HF) and iron deficiency (ID) have worse outcomes. Treatment with intra-venous (IV) ferric carboxymaltose has been shown to reduce HF rehospitalizations and to improve functional capacity and symptoms in patients with HF and reduced ejection fraction (HFrEF). However, IV ferric carboxymaltose is significantly more expensive than IV sodium ferric gluconate complex (SFGC) limiting its availability to most HF patients around the globe. Methods: A retrospective ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…This study is the first randomized trial to evaluate an IV iron supplement other than ferric carboxymaltose in patients with heart failure. In a previous retrospective study by our group, high-risk patients treated with IV SFGC had similar HF readmission rates, 5 which is in line with our results, showing comparable outcomes even with significantly higher levels of NT-proBNP at baseline. HF hospitalization rates were similar to those in the AFFIRM-AHF trial at the relevant time.…”
Section: Discussionsupporting
confidence: 91%
“…This study is the first randomized trial to evaluate an IV iron supplement other than ferric carboxymaltose in patients with heart failure. In a previous retrospective study by our group, high-risk patients treated with IV SFGC had similar HF readmission rates, 5 which is in line with our results, showing comparable outcomes even with significantly higher levels of NT-proBNP at baseline. HF hospitalization rates were similar to those in the AFFIRM-AHF trial at the relevant time.…”
Section: Discussionsupporting
confidence: 91%
“…It also massively reduced the risk of HF hospitalizations. On the contrary, Borreda and colleagues [ 22 ] showed that IV sodium ferric gluconate complex administration in AHF patients did not decrease the AHF readmission rate in a retrospective analysis.…”
Section: Reviewmentioning
confidence: 99%